KOMPETENSI BERBAHASA INDONESIA GURU SEKOLAH DASAR DI KALIMANTAN TENGAH (The Elementary School Teachers’s Proficiency of Bahasa Indonesia in Central Kalimantan) - R. Hery Budhiono (SALINGKA, 2017)
This research focuses on elementary school teachers proficiency of bahasa Indonesia in Central Kalimantan based on its average scores. The purpose of the research is to provide a comprehensive explanation of elementary school teachers proficiency in using bahasa Indonesia. The explanation given will be useful to decide what priority target and action should be taken. This research leans on the history of UKBI and descriptive statistics analysis. The writer uses note-taking technique in collecting data. The data in this research are UKBI scores. There are 185 samples in this research. The analysis is conducted in two ways, descriptively and statistically. Based on the findings, Kuala Kapuas reaches the highest average UKBI score. Meanwhile, Palangka Raya is the lowest. The writer also finds that region correlates strongly and significantly with UKBI scores.